Good functional outcome in patients suffering fragility fractures of the pelvis treated with percutaneous screw stabilisation: Assessment of complications and factors influencing failure. Issue 12 (December 2017) - Eckardt, Henrik; Egger, Alexander; Hasler, Rebecca Maria; Zech, Christoph J.; Vach, Werner; Suhm, Norbert; Morgenstern, Mario; Saxer, Franziska
Abstract: Background: Low energy pelvic ring fractures in the elderly have traditionally been treated conservatively, a treatment with potential long-term complications and loss of self-independence. Percutaneous screw stabilisation of the posterior pelvic ring is a new treatment modality that enables immediate mobilisation. The aim of this study was to assess the functional outcome after sacroiliac stabilisation in the elderly. Methods: All elderly patients with a surgically stabilised low energy pelvic fracture between 2010 and 2015 were included. In 2016 a radiographic follow up and functional test was performed at least one year postoperative. Results: The 50 operated patients had a mean age of 79 years and a one-year mortality of 10% (5/50). Only six patients lost independency after the pelvic fracture and moved to nursing home. The mean Timed Up and Go test was 16 s at follow-up. The operation of the posterior pelvic ring averaged 63 min with a radiation equal to a diagnostic pelvic CT. One intra-foraminally placed screw was immediately removed and 9 patients were later re-operated on due to symptomatic loosening of one or more screws. No loosening of screws was seen in 11 patients where both S1 and S2 were stabilised and out of 23 trans-sacral screws (crossing both sacroiliac joints) only two loosened. Discussion: CT guided stabilisation of the posterior pelvis is safe and most patients resumed good function and independent living. The risk of a revision operation was 20%, but trans-sacral screw stabilisation in both S1 and S2 could reduce the risk of implant loosening.